WOMEN in Latin America and the Caribbean in the 1990s. (1994)
Discusses (i) women in the regional scenario during the 1990s; (ii) gender equity using an integrated approach; (iii) living conditions of women in the 1990s. Stresses the need for political will to achieve gender equity, and the need for comprehensive inter-sectoral policies which address the task of alleviating poverty and include the dimension of gender equity.
DC